ANALISIS LAPORAN KEUANGAN PADA PRIMER KOPERASI POLISI (PRIMKOPPOL) WILAYAH LUMAJANG - Ayuningtyas, Triwilujeng; Wiranata, Roni (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2019)
Cooperative in Indonesia is a business entity that has an important element in the development of the Indonesian economy. Because cooperatives are business entities that are composed by the people and consist of people, the welfare of the people will increase. This is in accordance with the 1945 Constitution clause of 33 and paragraph in 1. The difference between cooperatives and other business entities is because cooperatives have multiple identities, namely as owners and users of cooperative services, therefore good management is needed, especially in their financial statements. Financial statements describe the financial position and health of a company. Therefore to know the financial condition can be seen from the level of Liquidity, Solvency, Profitability and efficiency of cooperatives in running the business. This study aims to determine the balance sheet and the remaining business results both to determine the capital turnover in the cooperative. The method used by collecting financial data so that developments in the cooperative will be known in a certain period. Therefore we need financial statement data to analyze it. The results of the research that can be concluded are the comparison of the balance sheet and the remaining operating results, for the number of balance sheets has increased by a percentage of 6.04% so that it will add to the increase in the remaining business results in other words labadip affected by the amount of service income increased due to increased sales of goods and total expenses reduced and other posts increased as well so that the remaining operating results have increased. Whereas the balance sheet increased in current assets and liabilities also increased. Then in the cooperative capital turnover also increased by 0.54% to 0.58% so that working capital is still well channeled.